Pengembangan Media Interaktif Matematika (Bangun Ruang Sisi Lengkung) untuk Meningkatkan Kemampuan Berpikir Geometri Siswa - Subadre, Wayan (Media Pendidikan Matematika, 2024)
Geometry learning is inseparable from students' geometric thinking abilities. However, most students acknowledge that geometry in mathematics is one of the most challenging subjects. This study focuses on the issue of geometric thinking abilities. To address this problem, the researcher attempted to use Interactive Mathematics Media (Curved Surface Solids) developed using GeoGebra software. This type of research is Research and Development (R&D) with the model proposed by Thiagarajan, known as the Four D Models (4D Model), which includes Define, Design, Develop, and Disseminate. The product developed by the researcher is Interactive Mathematics Media (Curved Surface Solids). The research sample consisted of 15 students from class IX-1 and 15 students from class IX-2 at SMPN 3 Tanjung, selected using purposive sampling techniques. The results of the study show that: (1) Interactive Mathematics Media (Curved Surface Solids) was deemed valid by experts with a score of 94.44, categorized as excellent; (2) Interactive Mathematics Media (Curved Surface Solids) received positive feedback in limited trials with a score of 85; (3) Interactive Mathematics Media (Curved Surface Solids) received positive feedback in effectiveness testing with a score of 82.59 and was found to be effective in teaching, with an average test score difference between the experimental and control classes of 11.34; and (4) Interactive Mathematics Media (Curved Surface Solids) can improve students' geometric thinking abilities, with an average geometric thinking ability score of 78.67.